RESENHA. BARANZINI, Mauro; MIRANTE, Amalia. A Compendium of Italian Economists at Oxbridge: Contributions to the Evolution of Economic Thinking - Teixeira, Joanílio Rodolpho (Informe Econômico (UFPI), 2020)
Resenha de livro